Late diagnosis of congenital toxoplasmosis based on serological follow-up: A case report. Issue 2 (April 2017) - Dard, Céline; Chemla, Cathy; Fricker-Hidalgo, Hélène; Brenier-Pinchart, Marie-Pierre; Baret, Marie; Mzabi, Alexandre; Villena, Isabelle; Pelloux, Hervé
Abstract: Toxoplasma gondii is a protozoan parasite infecting up to one third of the world's population. T . gondii infection is usually benign in immunocompetent patients but can be life-threatening when congenitally transmitted. Congenital toxoplasmosis presentation ranges from severe central nervous system and ocular features, to a well appearing newborn with onset of complications late in childhood. The diagnosis of subclinical form remains important since early treatment reduces later complications such as chorioretinitis. We report an atypical case of congenital toxoplasmosis with a delayed diagnosis, based on Toxoplasma -specific serological follow-up. The infant was born to a mother who became infected during pregnancy, thus inducing infant biological and clinical follow-up. Neither biological nor clinical arguments favored a diagnosis of congenital toxoplasmosis until ten months of life. Congenital toxoplasmosis was then suspected because of an unusual increase of specific IgG levels. Diagnosis was confirmed by detection of newly synthesized newborn Ig isotypes using complementary comparative mother-to-child immunological profile techniques and specific treatment therefore administered. This report highlights the importance to follow up newborns at risk of congenital toxoplasmosis with specific and newborn-appropriate techniques until Toxoplasma -IgG titers are completely negative. This allows not only the exclusion of congenital toxoplasmosis when serology becomes negative, but also the diagnosis and treatment of congenital toxoplasmosis when infection is detected later in development. Highlights: Specific and complementary techniques are needed for congenital toxoplasmosis diagnosis. Compared mother-to-child immune profiles favors early congenital toxoplasmosis diagnosis. Serological follow-up should be completed until T . gondii -IgG titers are completely negative.